2010
DOI: 10.1086/649885
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hepatitis B Virus Infection in a US Cohort of HIV‐Infected Individuals during the Past 20 Years

Abstract: Background The epidemiologic trends of hepatitis B virus (HBV) infection in HIV-infected patients over the last twenty years are largely unknown. Methods Prevalence and risk factors for HBV infection overall, at the time of HIV infection, and following HIV infection were examined in an ongoing observational HIV cohort study. Risk factors for HBV infection at the time of HIV diagnosis were evaluated using logistic regression, and risk for incident HBV infection following HIV diagnosis was evaluated using Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 34 publications
5
49
2
Order By: Relevance
“…In most Western countries, chronic hepatitis B (CHB) is frequently associated with HIV infection, with a 5-to 10-fold greater prevalence compared to the non HIV population, since 5% to 10% of HIV positive patients are chronically infected with HBV [1][2][3][4]. The impact and the perception of HBV-HIV co-infection have evolved over time, from a negligible problem overshadowed by the AIDS related illnesses, towards a genuine risk factor for increased morbidity and mortality [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…In most Western countries, chronic hepatitis B (CHB) is frequently associated with HIV infection, with a 5-to 10-fold greater prevalence compared to the non HIV population, since 5% to 10% of HIV positive patients are chronically infected with HBV [1][2][3][4]. The impact and the perception of HBV-HIV co-infection have evolved over time, from a negligible problem overshadowed by the AIDS related illnesses, towards a genuine risk factor for increased morbidity and mortality [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed a protective effect of HBVactive HAART, however included only very small numbers of individuals not on an HBV-active regimen. 9 A high proportion (35.9%) of cases had a history of IDU. A higher percentage of cases than controls had IDU exposure.…”
Section: Incident Hepatitis B Infectionmentioning
confidence: 99%
“…15,16 It has been shown that the incidence of chronic HBV infection has decreased since the HAART era. 9 Although we were unable to subdivide our group of patients between before and after the HAART era for analysis due to small numbers; it was evident that several cases of chronic HBV arose in the post-HAART era.…”
Section: Incident Hepatitis B Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this rate is more than 100-fold higher than in the general population [5]. In the USA, half of HIV-positive persons have been exposed to HBV, and exhibit markers of spontaneously self-limited HBV infection (HBV core antibodies [anti-HBc] with/without HBV surface antibodies [anti-HBs]) or have serum HBsAg+ [9].…”
Section: Introductionmentioning
confidence: 99%